Upaya Peningkatan Asupan Nutrisi Pada Anak Toodler Dengan Gizi Buruk - Annajiah, Fiah, Endang Zulaicha Susilaningsih, S.Kp., M.Kep (2017)
Background: malnutrition cases occur in developing countries such as Africa and Asia. Research results, then World Health Organization (WHO), which showed that as many as 53% of the causes of death of children under five are due to poor nutrition or malnutrition, two thirds were related to the lack of proper feeding. Malnutrition is a condition where the nutrient intake is insufficient to meet metabolic demands, and nutritional status based on weight for age index (weight/age) -3 SD. The impact of nutritional problems in children can affect the quality of the intelligence and the development of the future. Nutritional problems in children can also cause some negative effects such as slow growth of the body, prone to disease, reduced levels of intelligence, and the child's mental disturbance. Serious nutritional deficiencies can also cause death. Purpose: general purpose of writing a scientific paper is to describe efforts to improve nutrition in children with malnutrition. Special purpose to analyze the study of nutrition in children with malnutrition, analyzed interventions in improving nutrition in children with malnutrition, analyze about nutrition before and after implementation. Methods: in a scientific paper, the author uses descriptive method with case studies of nursing care for 6 days in Puskesmas Bulu Sukoharjo. Result: after the nursing care by providing health education on nutrition for parents, increased appetite, the patient is able to eat more than five tablespoons. Conclusion: to increase the appetite of the child, given the actions of health education on nutrition for parents, which one it is difficult to eat a child coping strategies. Required cooperation between parents and health care worker's client for the success of the nursing process.